2016
DOI: 10.1002/hrm.21813
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Multilevel Signals on Sex Discrimination Experiences Among Female Employees

Abstract: In this study, we examine the effect of organizational‐level and individual‐level signals on sex discrimination experiences, job satisfaction, and turnover intentions in a sample of South Korean female employees and organizations. Results indicate that the percentage of women employed in organizations was negatively associated with sex discrimination experienced by women. The number of family‐friendly policies was also negatively associated with sex discrimination in a panel design but not in a cross‐sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Other gender bias constructs also associate with job turnover. For instance, the literature has shown correlations between hostility and turnover intent (Kim, Longacre, & Werner, 2017). Workplace harassment, whether verbal abuse or sexual harassment, is a type of hostility grounded in repeated behaviors that intimidate, create discomfort, or alarm the victim.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…Other gender bias constructs also associate with job turnover. For instance, the literature has shown correlations between hostility and turnover intent (Kim, Longacre, & Werner, 2017). Workplace harassment, whether verbal abuse or sexual harassment, is a type of hostility grounded in repeated behaviors that intimidate, create discomfort, or alarm the victim.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…Relying on women's accounts of organisational experiences, exerting labour is used to mitigate occupational gender segregation. However, the actions the participants have taken may not necessarily be the best ways of improving human capital and career development (Kim et al, 2017). Thus, Kuo et al (2014) argue that increasing work efforts by constantly working longer hours often overtires employees psychologically and physically.…”
Section: Discussionmentioning
confidence: 99%
“…Relying on women’s accounts of organisational experiences, exerting labour is used to mitigate occupational gender segregation. However, the actions the participants have taken may not necessarily be the best ways of improving human capital and career development (Kim et al. , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Elliott and Smith (2001) posit that employers often demographically match managers with the workers they supervise to address workers' demands for representation, reduce conflict, and improve perceptions of fairness and equity. Consistent with this logic, research shows that women working for women managers are less likely to report experiencing gender discrimination than those working for men (Elliott & Smith, 2001; Stainback et al, 2011) or those in workplaces with more women generally (Yong Kim et al, 2017). Moreover, numerous studies have identified a strong relationship between nonmanagerial demographic composition and managerial representation (Bloch et al, 2021; Elliott & Smith, 2001).…”
Section: Gender Composition and Women's Managerial Representationmentioning
confidence: 94%
“…Pipeline effects may also impact nonadjacent positions. For example, Yong Kim et al (2017) suggest that as workplaces feminize, it may reduce the causal role of gender stereotypes in decision‐making throughout the organization.…”
Section: Gender Composition and Women's Managerial Representationmentioning
confidence: 99%